2021
DOI: 10.33448/rsd-v10i1.11903
|View full text |Cite
|
Sign up to set email alerts
|

Seedling quality of Agonandra brasiliensis in response to different Osmocote® doses and recipient volumes

Abstract: The objective of this work was to evaluate seedlings quality of the tree species Agonandra brasiliensis under different doses of the controlled release fertilizer (CRF) Osmocote® and recipient volumes. The experiment was set up in a factorial design for two recipient volumes (1.8 L and 2.2 L) and five CRF doses (0.0; 0.5; 1.0; 2.0; and 3.0 g L-1 of substrate). Four repetitions of one plant each were used. After transplanting seedlings, stem height, stem collar diameter, and the robustness index (RI) were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…It is observed that only potassium fertilization influences the PH/SD ratio, demonstrating a quadratic effect, with the dose of 77.50 mg dm-3 causing the lowest relationship between the variables. Mota et al (2021) mention that it is possible to monitor the quality of the seedling already implanted in the field using the variable mentioned above. For the SDM/RDM ratio, nitrogen fertilization was significant, resulting in a linear increase, indicating biomass allocation satisfactorily through the doses applied.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that only potassium fertilization influences the PH/SD ratio, demonstrating a quadratic effect, with the dose of 77.50 mg dm-3 causing the lowest relationship between the variables. Mota et al (2021) mention that it is possible to monitor the quality of the seedling already implanted in the field using the variable mentioned above. For the SDM/RDM ratio, nitrogen fertilization was significant, resulting in a linear increase, indicating biomass allocation satisfactorily through the doses applied.…”
Section: Resultsmentioning
confidence: 99%
“…The forestbased sector can be described as an important component of the Brazilian economy, because it contributes significantly to the gen eration of products, taxes, jobs and income (Smiderle et al, 2021 a). The growing expansion of this sector has driven forest investors to opt for the cultivation of native species in the state of Roraima (Smiderle et al, 2022).…”
Section: Introductionmentioning
confidence: 99%